2010
DOI: 10.1016/j.ijpara.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi I genotypes in different geographical regions and transmission cycles based on a microsatellite motif of the intergenic spacer of spliced-leader genes

Abstract: The intergenic region of spliced-leader (SL-IR) genes from 105 Trypanosoma cruzi I (Tc I) infected biological samples, culture isolates and stocks from 11 endemic countries, from Argentina to the USA were characterised, allowing identification of 76 genotypes with 54 polymorphic sites from 123 aligned sequences. On the basis of the microsatellite motif proposed by Herrera et al. (2007) to define four haplotypes in Colombia, we could classify these genotypes into four distinct Tc I SL-IR groups, three correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
107
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 62 publications
15
107
0
5
Order By: Relevance
“…More recently, León et al 56 suggested the subdivision of TcI only into two main groups (TcI DOM and sylvatic), proposing a PCR assay for identifying them. In the present study, the sequencing analysis of the TcI isolate (CT-IOC 541) showed that it is genetically closer to Sylvio X10, a stock identified as TcId 60 , a sub-group related to sylvatic cycles, which was also found by Câmara et al 38 in Northeastern Brazil. It is worth mentioning that TcId (or TcI sylvatic) was identified in the heart and brain of patients with severe Chagas disease outside Brazil 46,49 .…”
supporting
confidence: 80%
See 1 more Smart Citation
“…More recently, León et al 56 suggested the subdivision of TcI only into two main groups (TcI DOM and sylvatic), proposing a PCR assay for identifying them. In the present study, the sequencing analysis of the TcI isolate (CT-IOC 541) showed that it is genetically closer to Sylvio X10, a stock identified as TcId 60 , a sub-group related to sylvatic cycles, which was also found by Câmara et al 38 in Northeastern Brazil. It is worth mentioning that TcId (or TcI sylvatic) was identified in the heart and brain of patients with severe Chagas disease outside Brazil 46,49 .…”
supporting
confidence: 80%
“…Analysis of the spliced-leader intergenic region (SL-IR) of several TcI stocks evidenced five SL-IR groups (TcIa-TcIe) correlated with transmission cycles [57][58][59][60] . Other molecular studies displayed seven or three TcI subpopulations associated with their geographic distribution 54,61 .…”
mentioning
confidence: 99%
“…As a matter of fact, additional near-clades within TCI, which are stable, widespread and sometimes sympatric, have been labelled a to e . They have been corroborated by various markers (Cura et al, 2010;Ramírez et al, 2011). These lesser near-clades present some pathogenicity specificities (Llewellyn et al, 2009b).…”
Section: Parasitic Protozoamentioning
confidence: 59%
“…Por otro lado, de T. cruzi I se han descrito cinco subpoblaciones, las cuales se han identificado en una gran variedad de huéspedes, vectores y reservorios (66,67).…”
Section: Genotipos De Trypanosoma Cruzi Detectados En Los Brotes De Tunclassified